2021
DOI: 10.3390/ijms22052727
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of Volatile Anesthetic-Induced Organ Protection and Its Potential in Kidney Transplantation

Abstract: Ischemia reperfusion injury (IRI) is inevitable in kidney transplantation and negatively impacts graft and patient outcome. Reperfusion takes place in the recipient and most of the injury following ischemia and reperfusion occurs during this reperfusion phase; therefore, the intra-operative period seems an attractive window of opportunity to modulate IRI and improve short- and potentially long-term graft outcome. Commonly used volatile anesthetics such as sevoflurane and isoflurane have been shown to interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 186 publications
1
4
0
Order By: Relevance
“…Results from our study, which investigated the effects of three different VAs during general anesthesia in patients receiving a simultaneous pancreas and kidney transplantation (SPKT), are in line with previous findings obtained in the kidney [ 2 , 7 , 38 ], liver [ 6 ], and pancreas [ 9 ] transplant recipients. Anesthesia with sevoflurane and desflurane demonstrated graft protecting qualities by reducing IRI-associated postoperative complications.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Results from our study, which investigated the effects of three different VAs during general anesthesia in patients receiving a simultaneous pancreas and kidney transplantation (SPKT), are in line with previous findings obtained in the kidney [ 2 , 7 , 38 ], liver [ 6 ], and pancreas [ 9 ] transplant recipients. Anesthesia with sevoflurane and desflurane demonstrated graft protecting qualities by reducing IRI-associated postoperative complications.…”
Section: Discussionsupporting
confidence: 91%
“…This is particularly attributed to the volatile anesthetics (VA) used in our study and, to a lesser extent, to intravenous anesthetic agents [ 41 , 42 ]. With regard to the transplant setting, beneficial effects of VAs on IRI-associated consequences and improved graft outcomes could mainly be demonstrated in patients receiving a kidney or liver transplantation, with comparatively small differences between the study groups and also showing relatively short-lived and early improvements [ 2 , 6 , 7 , 8 , 38 ]. More recently, a study by Atoa et al demonstrated the protective effects of desflurane and sevoflurane compared with isoflurane in the first phase after SPKT, which were in line with our findings [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of hyaluronan increased significantly over time in the S-EVLP group but did not in the EVLP group. Hyaluronan is an important component of the extracellular matrix and one of the compounds of the glycocalyx, from which it can be released upon IRI or oxidative stress [35]. In an experimental set up with ex vivo perfusion of guinea pig hearts, treatment with sevoflurane showed a protective effect on glycocalyx integrity [24,25].…”
Section: Discussionmentioning
confidence: 99%